Решите уравнение и пишите как вы его решали: 12-2×(х+3)=26 заранее !

Rustam20022017 Rustam20022017    1   25.07.2019 04:30    0

Ответы
Chopykoe Chopykoe  24.09.2020 10:41
12-2×(х+3)=26
2*(х+3)=2х+6, т.к . перед 2 стоит минус будет -6
12-2х-6=26
-2х=26+6-12
-2х=20
х=-20:2
х=-10
можно проверить
12-2*(-10+3)=26
12-2*(-7)=26
12+14=26
26=26
ПОКАЗАТЬ ОТВЕТЫ
onealoner13 onealoner13  24.09.2020 10:41
12-2(х+3)=26 12-2х-6=26 -2х=26-12+6 -2х=20 -Х=10 Х=-10 ответ: -10.
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика